shr hʿdh ʾvrhm hkhhn hrṿfʾ vn ytsḥḳ vn frʾt / Abraham ha-kohen b. Isaac ibn Furat - Bareket, Elinoar (Hebrew Union College annual, 1999)
New research on Jewish leaders in the Fatimid Kingdom, along with a re-examination of related documents, has made it possible to compile a list of persons who served as rais al-yahud (Head of the Jews) in the Fatimid Kingdom in Egypt since it was conquered by the caliphs. It can be seen that the kind of people who held this office changed according to the changing circumstances and needs of the caliphs. The first to hold the office were Rabbanites who obtained their position as a direct result of their status as court physicians. In the first half of the eleventh century, after a period of decline in the importance and power of the office during the reign of Caliph al-Hakim, the office was held by Karaites, who were great merchants and whose services were needed by the caliph. In the last third of the eleventh century the office returned to Rabbanite court physicians. This list is still disputable and incomplete. It is unclear who held the office in the fifth and sixth decades of the century. In documents found in the Geniza the name of Abraham ha-Kohen b. Isaac ibn Furat stands out. Born in Fustat, and a physician like his father, he served many years as the Fatimid governor's physician in Ramla. By collecting what is already known about this man, and adding new information, it is possible to assume that he was the rais al-yahud in the fifth and sixth decades of the eleventh century. This assumption could well complete the picture of Jewish leadership in Fatimid Egypt, as well as adding to the understanding of the relationship between the rais al-yahud in Egypt and the Head of the Palestine Yeshiva, the Gaon.